Digital Anki Flashcards for Improving Mandarin Vocabulary Mastery in Grade VIII - Armus, Putri Rakhmadina; Achmad, Abdul Kasim; Mustarih, Nirdayanti (Universitas Negeri Semarang, 2025)
Vocabulary mastery is a crucial component in learning foreign languages, including Mandarin, which is increasingly important in today's global context. However, junior high school students in Indonesia often struggle to master Mandarin vocabulary successfully, partly due to the limited use of interactive digital learning media. This study aims to describe the use of digital-based Anki flashcard media and examine its impact on the vocabulary mastery of eighthgrade students at SMP IT Cheng Hoo. Using the Classroom Action Research (CAR) model by Kemmis and McTaggart, the research was conducted in two cycles involving 17 students. Data were collected through vocabulary tests and observation sheets. The findings revealed an improvement in the average student score from 60.78 in the first cycle to 85.09 in the second, indicating a 24.31-point increase. These results suggest that the use of Anki significantly supports students' retention and understanding of Mandarin vocabulary. The study concludes that digital flashcard applications like Anki offer an innovative and responsive learning strategy that suits students' needs and increases engagement in Mandarin vocabulary acquisition.